Primary malignant melanoma of the gastroesophageal junction with KIT gene exon 11 mutation - Gao, Xiaozhuo; Zhao, Zehua; Zhu, Yanmei (Journal of the Pakistan Medical Association, 2024)
Mucosal melanoma (MM) represents an uncommon form of melanoma. Primary gastrointestinal tract (GIT) melanoma is even rarer. A 70-year-old male visited the Liaoning Cancer Hospital and Institute, China, due to upper abdominal discomfort for the past two months. His endoscopy revealed a prominent, 6-cm ulcerated neoplasm in the gastroesophageal junction (GEJ). Lesion endoscopic biopsy showed diffusely distributed tumour cells. He underwent subtotal gastrectomy with lymph node dissection (LND). Postoperative histopathology revealed a diffuse distribution of tumour cells with numerous tumour-infiltrating lymphocytes (TILs) and pigment granules. Immunohistochemical (IHC) results were positive for both S-100 and HMB-45. Molecular analysis showed KIT gene exon 11 mutations. Although the clinicians emphasised the necessity of systemic chemotherapy and immunotherapy with the patient and his family, the patient did not receive any adjuvant therapy and died 36 months after surgery. —Continue